Kurashha.co : Shaw Bottle Crusher / Aizat Fathullah Azman ...[et al.] - Azman, Aizat Fathullah; Noor Hesham, Suraya Nabilah; Sa'adon, Muhammad Issafeeqa; Mohd Masri, Muhamad Bhauddin; Omar, Alif Azri (2017)
KURASHHA Co. is a small company that produce and sell pet bottles crusher at an affordable price. The company is established to encounter the problem faced by the public which is to ease people to recycle pet bottles and keep surrounding place clean.